Pemanfaatan Instrumen Tes dan Nontes Pada Layanan Konseling di Kabupaten Padang Lawas - Ade Chita Putri Harahap; Azura Mahyuliza Sembiring,; Hilda Amaliyah Lubis; Irma Suryani Nasution; Lenni Dalimunthe (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to reveal how counseling teachers or counselors can use instruments in schools, both test and non-test. From the data collected, it was obtained information that when providing services the Bk teacher only used the test instrument by giving several questions to determine the cognitive level but not the affective and psychomotor or so-called non-test instruments. This study uses a qualitative method, the data used for this research is using a Computer Questionnaire (Questionnaire via online/online). are in rural areas. The benefit of this research is that the counseling teacher or counselor can evaluate themselves and to be able to add insight to what is not yet known about test and non-test instruments. Keywords: instrument test, counseling service